SYSTEMS AND VALUE-BASED APPROACH SYNTHESIS IN THE PROCESS OF STRUCTURAL MODERNIZATION OF ENTERPRISES - K. A. Gusev (Real Economics Publishing House, 2014)
The article analyzed the dynamics of stock prices in five years and identified the factors most market capitalization growth OJSC “AvtoVAZ” and OJSC “KamAZ”. Reviewed the concept of structural modernization of the enterprise as a tool to implement its strategy. It is the structural modernization of enterprises is an effective tool of improving their fair value and market capitalization in the medium and long term period.